Using Peer Review with Greek EFL College Students - Ilkos, Melpomeni (Journal of Academic Writing, 2018)
Peer review fosters student critical thinking and self-evaluation (Wood and Kurzel 2008). Numerous studies show that peer review is effective in improving student writing (Althauser and Darnall 2001, Bean 2011), and that it benefits the students receiving as well as those giving the feedback (van den Berg, Admiraal and Pilot 2006). However, these issues have not been greatly researched in Greece. Greek culture bestows great authority to the teacher and students are not accustomed to peer feedback. I have embarked on a small-scale, exploratory, classroom-based study conducted at Deree - The American College of Greece where English is the medium of instruction. Data include first and revised drafts of three academic writing assignments, written peer comments, and learner reflections on the peer reviewing experience. To further explore student attitudes toward peer review, I also administered an online questionnaire. Initial quantitative and qualitative analyses reveal (a) in general student reviewers and reviewees alike accept peer review as an appropriate pedagogical activity; (b) students revise their writing taking into account peer feedback and (c) as reviewers, students were not more critical in giving feedback when doing peer review anonymously. Preliminary results are interpreted with an understanding of the limitations of the ongoing study.